Optimalisasi Kompetensi Keberlanjutan: Analisis Reliabilitas dan Validitas Asesmen Pra-Pembelajaran Siswa Sekolah Menengah Pertama - Ismail, Ismail; Isnawati, Isnawati (Jurnal Didaktika Pendidikan Dasar, 2024)
The development of pre-learning assessments integrating the Minimum Competency Assessment (AKM) with Education for Sustainable Development (ESD) content is crucial for equipping students with the necessary knowledge and skills to tackle global challenges. This study aims to create a pre-learning assessment instrument that combines AKM and ESD for Business and Energy materials targeted at grade VIII Junior High School students. The study’s participants included students from grades VII to IX to test the instrument’s generality, utilizing the 4-D model by Thiagarajan et al., comprising definition, design, development, and deployment phases. The final product is a pre-learning assessment instrument tailored for grade VIII semester 2. Data analysis employed qualitative and quantitative descriptive methods using the Rasch model via Winstep 5.7.1 software. Additional analyses, including data triangulation and in-depth interviews with students and teachers, enriched the interpretation of results. The findings revealed that the instrument met high-quality criteria, with an average validation score of 2 (excellent), an instrument reliability of 0,98 (special category), a person reliability of 0,85 (good category), content validity meeting set requirements, and construct validity ranging from 0,53 to 0,71, indicating overall validity.